Robust Quantum Key Distribution Based on Two Level Qdna Technique to Generate Encrypted Key - Srilatha, N; Deepthi, M; Rajasekhar Reddy, I (International Journal of Computer Sciences and Engineering, 2025)
The Privacy is paramount when communicating subtle information, and humans have devised some unusual ways to encode their conversations. The Quantum Key Distribution agrees for the secure transmission of unbreakable encryption keys and it provides a flawless secure coding to solve the problem of key distribution. At present this is more mature application in the field of quantum computing. The fundamental concept of this protocol involves two parties, wishing to exchange a key both with access to a classical public communication channel and a quantum communication channel. The entanglement distillation approach of BB84 is widely used because the act of reading a quantum bit (QuBits) changes the bit, it is difficult for hackers to interfere without being detected sufficient number of bits. But this technique uses only four directions of electron movements so it is possible to guess the key. To overcome these drawbacks here two level QRNA technique is proposed for security. In first level DNA is applied on plain text after BB84 protocol is applied. This method provides better security than both BB84 protocol and DNA alone.